Implementasi Metode Diskusi dalam Mengoptimalkan Prestasi Belajar Siswa Kelas X pada Mata Pelajaan Aqidah Akhlak di MAN 2 Sinjai - Suriyati, Suriyati; Kahar, Kahar; Jamaluddin, Jamaluddin; P, Sudirman.; Sudarsifa, Nurul Annisa (Universitas Muhammadiyah Surabaya, 2024)
This research aims to investigate the effect of the discussion method in increasing the learning achievement of class X students at MAN 2. The type of research used is qualitative research and uses the library research method. The data collection techniques used in this research used interviews, observation and documentation. After the data is collected, it is then analyzed by collecting data, reducing data and drawing conclusions. From the results of the researcher's analysis, it shows that. The discussion method applied by the teaching staff at MAN 2 Sinjai is very well implemented because by applying this method students can carry out the process of exchanging opinions with other students, every student who can be active in using this discussion method can gain many benefits if they are active in the process, because this method really helps students to continue to think critically, practice public speaking, and provide their thoughts and ideas. So, by maximizing the implementation of the discussion method, it is hoped that students can achieve learning goals more effectively and efficiently